2021
DOI: 10.1080/09638288.2021.1927207
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to post-stroke homonymous hemianopia – a prospective longitudinal cohort study to identify predictive factors of the adaptation process

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…The participants in this research frequently described changes to their lives after their neurological diagnosis that often centred around adapting (where possible) to their visual impairments, and becoming actively involved in research studies and peer support groups. This finding concurs with previous research into stroke survivors’ adaptation of visual field loss, which suggested that adaptation is an individual process and changes to meet the needs of the environment and task, with the authors promoting that early diagnosis and management should be offered to these patients to support them in adapting [ 33 ].…”
Section: Discussionsupporting
confidence: 90%
“…The participants in this research frequently described changes to their lives after their neurological diagnosis that often centred around adapting (where possible) to their visual impairments, and becoming actively involved in research studies and peer support groups. This finding concurs with previous research into stroke survivors’ adaptation of visual field loss, which suggested that adaptation is an individual process and changes to meet the needs of the environment and task, with the authors promoting that early diagnosis and management should be offered to these patients to support them in adapting [ 33 ].…”
Section: Discussionsupporting
confidence: 90%
“…Given the large impact of driving on QoL, evaluation for driving safety and rehabilitation may offer a simple and cost‐effective method of improving CB patients’ QoL. In addition, a subset of patients may adapt well enough to their deficit to return to driving, regardless of intervention (Howard et al., 2022 ). Finally, we note that pass/fail results for on‐road testing and simulator environments show good fidelity in CB patients (Ungewiss et al., 2018 ), suggesting that simulated tests could provide a safe, naturalistic space for examination of CB driving ability (Bowers, 2016 ; Bowers et al., 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective observational case cohort study, adult stroke survivors with new onset homonymous hemianopia were recruited. The measurement of saccade parameters using a head-mounted infrared eye tracker (Saccadometer Advanced LatencyMeter 6.5, Ober Consulting SN 1152) was attempted for all study participants as part of a comprehensive assessment of visual and navigational functions (Howard et al 2021). Participant demographics that included age, gender, ethnicity and postcode were collected.…”
Section: Methodsmentioning
confidence: 99%
“…The primary aim of the overall research study was to investigate the factors important for adaptation to post-stroke homonymous hemianopia (Howard et al 2021). As a secondary objective, we investigated saccade parameters of participants recruited to this UK-based clinical study.…”
Section: Introductionmentioning
confidence: 99%